High dose simvastatin and adverse muscle effects - Yenny, Yenny (Faculty of Medicine, Trisakti University, 2011)
High blood cholesterol, or hyperlipidemia, is a cardiovascular risk factor. Surveys have demonstrated that 35.6% of adults in the United States suffer from hyperlipidemia.(1) Currently there are various therapeutic regimens available for hyperlipidemia. The use of lipid-lowering drugs, patient education, dietary modification, and exercise have all been recommended for the management of hyperlipidemia.